2012
DOI: 10.1037/a0028924
|View full text |Cite
|
Sign up to set email alerts
|

Mismatched expressions decrease face recognition and corresponding ERP old/new effects in schizophrenia.

Abstract: Objective:The objective was to investigate the electrophysiological (ERP) correlates of mismatched expression on face recognition in schizophrenia. Method: Expression-change effects and associated ERPs were explored in patients with schizophrenia (n ϭ 20) and paired comparison participants (n ϭ 20) on a long-term face-recognition task. Results: A facial-expression change decreased discriminability for patients with schizophrenia than for healthy participants. The patients' recognition deficit was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…By demonstrating a familiarity deficit with highly conceptual material such as common objects, the present study is in line with the finding in other studies that dual process estimates are modulated by different types of contextual manipulations (e.g., Clark and Gronlund, 1996;McKenzie and Tiberghien, 2004), and adds support to the proposal of a familiarity deficit in schizophrenia specifically in conditions of study-test perceptual mismatch (Guillaume et al, 2007(Guillaume et al, , 2012a(Guillaume et al, , 2012b. In line with this proposal, much caution is warranted about the drawing of a straightforward distinction between a contextually based recollection and acontextually based familiarity.…”
Section: Familiarity and Recollection Deficitssupporting
confidence: 86%
See 1 more Smart Citation
“…By demonstrating a familiarity deficit with highly conceptual material such as common objects, the present study is in line with the finding in other studies that dual process estimates are modulated by different types of contextual manipulations (e.g., Clark and Gronlund, 1996;McKenzie and Tiberghien, 2004), and adds support to the proposal of a familiarity deficit in schizophrenia specifically in conditions of study-test perceptual mismatch (Guillaume et al, 2007(Guillaume et al, , 2012a(Guillaume et al, , 2012b. In line with this proposal, much caution is warranted about the drawing of a straightforward distinction between a contextually based recollection and acontextually based familiarity.…”
Section: Familiarity and Recollection Deficitssupporting
confidence: 86%
“…The dissociation between priming and explicit memories could be critical in schizophrenia (Gras-Vincendon et al, 1994) where study-test perceptual mismatch disturbs patients' recognition to a greater extent than controls (Guillaume et al, 2012a(Guillaume et al, , 2012b. Impaired inhibition of irrelevant information has been associated with disorganization symptoms such as thought disorders (Baxter and Liddle, 1998;Bazin et al, 2000;Guillem et al, 2003;Guillaume et al, 2012a), whereas the source memory impairment is thought to be a key determinant of hallucinations and delusions, i.e., the most common symptoms of schizophrenia (Bentall, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, a number of studies offer strong support for the claim that the FN400 is not limited to conceptual priming or amodal familiarity (Bridger et al, 2012;Mecklinger et al, 2012;Rugg and Curran, 2007). For example, changes in the magnitude of the mid-frontal old-new effect have been observed using manipulations of perceptual congruency between study and test (Groh-Bordin et al, 2006;Guillaume et al, 2012b;Speer and Curran, 2007;Tsivilis et al, 2001) or perceptual manipulations (such as the background in object or face recognition) that seem unlikely to be explainable in terms of changes in conceptual priming (Ecker et al, 2007a,b;Guillaume et al, 2012a). Tsivilis et al (2001) reported a contextual sensitivity of familiarity (to object background) as reflected by the FN400 effect, and concluded that the effect indexes some process "downstream" from familiarity.…”
Section: Introductionmentioning
confidence: 95%
“…A common finding is that correctly rejected new items elicit more negative-going FN400 than correctly recognized old ones (Nessler et al, 2005;Rugg and Curran, 2007;Tsivilis et al, 2001). The FN400 is also modulated by study-test mismatches, such as expression change with face recognition (Guillaume et al, 2012a) or color change with object recognition (Ecker et al, 2007a,b). The link between the FN400 and familiarity seems so obvious that some authors have even concluded that familiarity occurs whenever an FN400 effect is observed (Curran and Cleary, 2003;Rugg and Curran, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…While a number of ERP investigations on episodic memory formation have been conducted in schizophrenia, they have tended to focus on the aspect of retrieval mechanisms (1,2). There is only 1 ERP study, to the best of my knowledge, that examined episodic encoding.…”
mentioning
confidence: 99%